2015
DOI: 10.1080/03670244.2015.1072813
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes and lifestyle patterns of Korean children and adolescents with atopic dermatitis: Using the fourth and fifth Korean National Health and Nutrition Examination Survey (KNHANES IV,V), 2007–11

Abstract: We investigate dietary intake and lifestyle patterns of atopic children and adolescents (N = 539) by obesity level using a national survey of South Korea. Intakes of calcium, iron, and vitamin C in the underweight group were less than those of other groups. The frequency of drinking milk of the overweight group was higher than that of the normal weight group. Majority of the subjects had not applied nutrition labeling in food choices, had no experience of nutrition education, and were vitamin D deficient. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Also, in large population-based studies, it was observed that there is an increased likelihood of developing AD in individuals with either deficient or insufficient vitamin D levels [117,118]. Many observational studies including a meta-analysis have shown that the serum vitamin D level is lower in children and adults with AD compared to controls, and reported an association between vitamin D deficiency and risk of atopic eczema [119,120,121]. Also, the severity of AD was found to be negatively correlated with the vitamin D level, with moderate and severe AD groups having lower vitamin D levels compared to the mild AD group; this finding was supported by the use of objective tools, such as the SCORAD (Scoring Atopic Dermatitis) index, which was found to be inversely correlated with vitamin D levels in AD patients [120,121,122,123].…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Also, in large population-based studies, it was observed that there is an increased likelihood of developing AD in individuals with either deficient or insufficient vitamin D levels [117,118]. Many observational studies including a meta-analysis have shown that the serum vitamin D level is lower in children and adults with AD compared to controls, and reported an association between vitamin D deficiency and risk of atopic eczema [119,120,121]. Also, the severity of AD was found to be negatively correlated with the vitamin D level, with moderate and severe AD groups having lower vitamin D levels compared to the mild AD group; this finding was supported by the use of objective tools, such as the SCORAD (Scoring Atopic Dermatitis) index, which was found to be inversely correlated with vitamin D levels in AD patients [120,121,122,123].…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Vitamin D also plays a vital role in the development of certain inflammatory skin diseases. Many observational studies, including a meta-analysis, have found that levels of serum vitamin D are lower in adults and children with atopic dermatitis (AD) than in controls and that vitamin D insufficiency is linked to the risk of atopic eczema [61][62][63]. Many investigations have found a shortage or insufficiency of serum vitamin D in psoriatic patients, indicating that vitamin D plays an important role in the disease [64,65].…”
Section: Role Of Vitamin Dmentioning
confidence: 99%
“…Furthermore, vitamin D treatment can dampen the enhanced IgE response in AD by lowering the IgE production by human B cells and suppressing IgE-mediated mast cell activation [ 238 ]. Many case-control studies have shown a lower level of vitamin D in AD subjects compared to controls and the association of vitamin D deficiency to a more severe course of the disease [ 239 , 240 , 241 ]. In a prospective cohort study, it was observed that vitamin D-deficient individuals have an increased likelihood of developing AD [ 242 ].…”
Section: Molecular and Clinical Studies Of Vitamin D In Various Dimentioning
confidence: 99%